Девушка из нежной стали: роман / Татьяна Алюшина - Алюшина Татьяна Александровна (Еще раз про любовь, 2018)
Экземпляры: К.Х. (20200313) / Инвентарный номер: 47722 / Цена: 132.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: А 59 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44